Case Report: Morbihan disease treated with tofacitinib successfully - Li, Zi-Yun; Chi, Chao-Cheng; Cai, Sui-Qing (Frontiers in Immunology, 2023)
To date, there is no standard treatment for Morbihan disease. Several studies have reported that Morbihan disease responds well to systemic corticosteroids (prednisone and prednisolone, systemic antibiotics (tetracyclines), antihistamines (ketotifen), and surgical therapy (Lymphaticovenous anastomosis). To our knowledge, Tofacitinib, as a Janus Kinase (JAK) inhibitor, plays a vital role in the treatment of inflammatory and autoimmune disorders. Therefore, Tofacitinib may be a promising medical option for patients with Morbihan disease.